1997
DOI: 10.1287/mnsc.43.6.856
|View full text |Cite
|
Sign up to set email alerts
|

The Influence Prism in SMEs: The Power of CEOs' Perceptions on Technology Policy and Its Organizational Impacts

Abstract: The research proposes a model, which relates the following variables: (a) the CEO's perceptions of the environment, (b) the strategic business orientation, scanning, and structural characteristics, (c) technology policy, (d) realized innovative efforts of the firm, and (e) measures of firm performance. The empirical data from small manufacturing enterprises (SMEs) that share a common economic and industrial environment show that CEOs' perceptions of external environment---and not objective measures---are key s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0
18

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(108 citation statements)
references
References 56 publications
4
86
0
18
Order By: Relevance
“…The list provided access to data such as a company's location and the name and e-mail address of its CEO. The chief executive officer was selected as the single informant as he or she acts as the ''principal architect of corporate strategy'' (Harrison 1992), including technological choices and investments (Lefebvre et al 1997). CEOs of the selected firms were reached by e-mail and asked to participate in an on-line survey.…”
Section: Population and Data Collectionmentioning
confidence: 99%
“…The list provided access to data such as a company's location and the name and e-mail address of its CEO. The chief executive officer was selected as the single informant as he or she acts as the ''principal architect of corporate strategy'' (Harrison 1992), including technological choices and investments (Lefebvre et al 1997). CEOs of the selected firms were reached by e-mail and asked to participate in an on-line survey.…”
Section: Population and Data Collectionmentioning
confidence: 99%
“…Mohr (1969) has also referred to a moderating effect of the size of the firm on the relative importance of its determinants of innovation. For example, top management characteristics and attitudes were found to be more important innovation determinants for small firms, due to the more active involvement of top managers in the innovation process (Carrier, 1994, Lefebvre et al, 1997.…”
Section: 2) the Management Perspective: Determinants Of Innovationmentioning
confidence: 99%
“…There is a slower adoption of IT in SMEs than in large enterprises (Lia et al 2004, Premkumar 2003. Existing mechanisms of IT governance build on a strong belief that IT creates values for the business; but these do not hold true for SMEs where decision making is mostly centred round one person (Levy et al 2003, Southern et al 2000, Lefebvre et al 1997. SMEs also cannot learn and benefit from past experiences because there are not enough IS projects conducted.…”
Section: Outsourced Is Failures In Smesmentioning
confidence: 99%
“…In this research, we focus on two major findings: the role of the CEO as the principal decision maker in SMEs (Southern et al 2000;Lefebvre et al 1997) and the dependency of SMEs on external IT expertise (Thong 2001, Thong et al 1997). Thong has shown that both findings are related: "The results show that the most effective IS implementation environment is one in which both top management support and external IS experts work as a team".…”
Section: Outsourced Is Failures In Smesmentioning
confidence: 99%